Extranodal pulmonary marginal zone B-cell lymphoma - CEYHAN, BERRİN; OLGUN YILDIZELİ, ŞEHNAZ (ELSEVIER SCIENCE BV, 2016)
Aim: Extranodal mucosa-associated lymphoid tissue (MALT) arises a number of epithelial tissues, including the stomach, salivary gland, lung, small bowel, and elsewhere. Here we present a male patient with an uncommon site of extranodal MALT such as a pelvic mass diagnosed after a long period of evaluation, which initially presented with an incidental pulmonary nodule. Method: We report a 60 years old man presenting with pulmonary nodules and consolidation. He refused invasive procedures and 3 years later was administered to our clinic with disseminated pulmonary nodules on chest X-ray. Subsequently a thin needle aspiration biopsy was performed and candida geotrichum was suspected in the specimen of the lung biopsy by light microscopic examination. After this time the patient was referred to our clinic, bronchoscopy, mediastinoscopy and abdominal computerized tomography (CT) scans were performed. Results: Lymphoid hyperplasia was seen in the mediastinal lymph nodes biopsy specimens and the pelvic mass (52 x 18 mm) on the superior iliac muscles not related to any organs. Thin needle biopsy revealed MALT lymphoma and pathological examination of pulmonary nodule was similar to pelvic mass (MALT lymphoma). After the diagnosis, the thin needle biopsy of lung was repeated. The specimen appeared to be similar to the pelvic mass (MALT lymphoma) in the pathologic examination. The patient survived 5 years after initial diagnosis. Conclusion: MALT has an affinity for the different tissues however has not been located in the pelvis. Our case represent an unusual presentation in a 60 years old man with lung and a pelvic mass. (C) 2016 Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license.
Keywords: Pulmonary; B-cell; Lymphoma